The Infrared Traced Star Formation Rates of Associated Absorption Lines Quasars - Zhe-Geng Chen; Rui-Jing Lu; Zhi-Fu Chen; Wen-Qiang Liang; Xing-Long Peng; Jing Li; Wei-Rong Huang (The Astrophysical Journal)
Some optically selected quasars exhibit Mg ii- associated absorption lines (AALs), and their origin remains unclear. In this paper, we compile a sample of 1769 quasars, with or without Mg ii AALs, of which 1689 are far-infrared (FIR) detected quasars and the rest are not detected in FIR. For the FIR undetected quasars, we obtain stacks for both with and without Mg ii AAL quasars. Then, we estimate the star formation rates (SFRs) within quasar host galaxies based on their FIR luminosities derived from their FIR graybody components, and find that, although quasars with Mg ii AALs have significantly redder median composite spectra than those without Mg ii AALs, the SFR distributions of the two types of quasars are statistically indistinguishable. These results do not require an evolutionary link between the quasars with and without Mg ii AALs, and would be reconciled if an orientation effect cannot be ignored among the quasars hosting different types of absorption lines.